2019
DOI: 10.20517/2394-4722.2019.14
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic and predictive role of hyponatremia in cancer patients

Abstract: Hyponatremia is the most frequent electrolyte disorder encountered in hospitalized patients. Several studies have demonstrated that hyponatremia is a negative prognostic factor in different clinical scenarios. Noteworthy, not only severe and acute hyponatremia has been associated with an increased risk of mortality, but also moderate of even mild chronic hyponatremia may increase the risk of death. This has been demonstrated in different categories of patients, including cancer patients. There is growing evide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 44 publications
0
7
1
Order By: Relevance
“…The evolution of serum creatinine together with SNa is also a good parameter. Serum creatinine usually increases when natremia drops in the hypovolemic patient and usually decreases along with hyponatremia in the euvolemic patient [14] .…”
Section: Physical Examination Orthostatismmentioning
confidence: 99%
See 3 more Smart Citations
“…The evolution of serum creatinine together with SNa is also a good parameter. Serum creatinine usually increases when natremia drops in the hypovolemic patient and usually decreases along with hyponatremia in the euvolemic patient [14] .…”
Section: Physical Examination Orthostatismmentioning
confidence: 99%
“…Additional treatments for hyponatremia must be avoided during the first 24 h of correction, except for associated furosemide in patients with heart failure or the addition of potassium chloride in patients with initial hypokalemia [2,14] [ Table 5] [22] .…”
Section: A Patient Who Is a Candidate For Chemotherapymentioning
confidence: 99%
See 2 more Smart Citations
“…Based on literature reports, hyponatremia and SIADH appear to be important negative predictive factors of mortality in numerous medical conditions, including lung cancer [4,9,12,[18][19][20][21][22], but not in every paper reached this conclusion [6,10]. However, a recent meta-analysis of fifteen studies confirmed the prognostic significance of serum sodium levels by demonstrating that the correction of hyponatremia is associated with reduced risk of mortality in hospitalized oncology patients [23].…”
Section: Introductionmentioning
confidence: 99%